Exploring Interactive and Innovative Learning Media in EFL Classroom: A Students' Perspective - Donny Adiatmana Ginting (The Seall Journal, 2023)
The study on the shift to online learning in English language education due to the COVID-19 pandemic. The study examines the perceptions of twenty English Department students from STKIP Al Maksum regarding the use of interactive applications, particularly Kahoot, in their learning. A quantitative survey with a ten-item questionnaire was employed to gather data. The findings suggest that students perceive Kahoot as enhancing their enjoyment, learning perception, effectiveness, and motivation. The study concludes that applications like Kahoot and Quizzes contribute to increased student activity in language classes and highlights the need for further research on their impact on critical thinking, engagement, and educational outcomes.